Метод исследования магнитного поля источника - Рудас, Юрий Данилович; Лупиков, Валерий Сергеевич (НТУ "ХПИ", 2003)
Разработан инженерный метод определения параметров поверхности второго порядка с постоянной величиной индукции – изодинамы магнитного поля, создаваемого мультипольным источником. Экспериментальные данные получают для фиксированного значения индукции на трех параллельных плоскостях, расположенных с одной стороны от источника. Метод позволяет уменьшить объем экспериментальных данных при анализе распределений магнитного поля протяженных технических объектов.

The analysis of the second order surface, representing 3D distribution of the multypole source magnetic field with constant value of induction is fulfilled. The engineering method for determination of geometrical parameters of the surface is developed. As initial dates of measuring induction on three parallel planes located in relation to the source from one side are used. The method allows minimizing the volume of measuring date at the analysis of magnetic field produced by long technical objects.
Analyses of magnetic field produced by multypole source
Keywords: индукция; изодинама; магнитное поле; инженерный метод; моделирование; technical object; multypole source; magnetic field; distribution; analyses method